“Like a Half-Crushed Worm”: Affliction, Negative Capability, and Apophatic Aesthetics in the Work of Nuclear Death - Butler, Daniel (Théologiques)

(untitled) (Faculté de théologie et de sciences des religions, Université de Montréal, 2018)
This paper turns to Arizona-based band Nuclear Death (1985-2000) as a case of apophatic aesthetics in extreme metal. Amador Vega’s “apophatic aesthetics” offers a framework for theorizing formlessness as preamble to form’s emergence. Emergent forms of “love” and “justice” in Nuclear Death’s work are discussed in reference to Michele Toscan’s biographical sketch of the band. Invoking the concepts of affliction and negative capability, and their respective elaboration by philosopher-mystic Simone Weil and psychoanalyst Wilfred Bion, I argue Nuclear Death do not praise or curse God, but dwell in God’s absence, suffering a state of affliction that leaves the listener “struggling on the ground like a half-crushed worm.” Bion’s negative capability and Weil’s emphasis on self-annihilation are cast as ascending and descending views of desire, and together accent different aspects of Nuclear Death’s first two albums, Bride of Insect (1990) and Carrion for Worm (1991). Lastly, I suggest that Nuclear Death invite a tragicomic response to the absurdity of affliction, which contrasts with the solemnity found in Weil’s and Bion’s works.